A Zebrafish Model of Metastatic Colonization Pinpoints Cellular Mechanisms of Circulating Tumor Cell Extravasation - Allen, Tyler A.; Cullen, Mark M.; Hawkey, Nathan; Mochizuki, Hiroyuki; Nguyen, Lan; Schechter, Elyse; Borst, Luke; Yoder, Jeffrey A.; Freedman, Jennifer A.; Patierno, Steven R.; Cheng, Ke; Eward, William C.; et al. (Frontiers in Oncology, 2021)
Metastasis is a multistep process in which cells must detach, migrate/invade local structures, intravasate, circulate, extravasate, and colonize. A full understanding of the complexity of this process has been limited by the lack of ability to study these steps in isolation with detailed molecular analyses. Leveraging a comparative oncology approach, we injected canine osteosarcoma cells into the circulation of transgenic zebrafish with fluorescent blood vessels in a biologically dynamic metastasis extravasation model. Circulating tumor cell clusters that successfully extravasated the vasculature as multicellular units were isolated under intravital imaging (n = 6). These extravasation-positive tumor cell clusters sublines were then molecularly profiled by RNA-Seq. Using a systems-level analysis we pinpointed downregulation of KRAS signaling, immune pathways, and extracellular matrix (ECM) organization as enriched in extravasated cells (p < .05). Within the extracellular matrix remodeling pathway we identified versican (VCAN) as consistently upregulated and central to the ECM gene regulatory network (p < .05). Versican expression is prognostic for poorer metastasis-free and overall survival in patients with osteosarcoma. Together, our results provide a novel experimental framework to study discrete steps in the metastatic process. Using this system we demonstrate versican/ECM network dysregulation as important to osteosarcoma circulating tumor cell extravasation.